An Empirical Study on the Core Competencies of College Counselors in China - Shibang, Long; Shaogang, Yang; Huiyi, Chen (ETHICS IN PROGRESS, 2020)
From the perspective of empirical research, this paper conducts a specific study on the core competencies of college counselors. 450 participants from 4universities participated the research. A questionnaire of college counselors’ core competencies from the aspects of the design of an open questionnaire was designed and implemented, a predictive questionnaire was tested and analyzed, and a formal questionnaire was implemented. The results of the formal questionnaire show that component one mainly concerns ideological awareness and values, component two mainly concerns professional ethics, moral accomplishment, quality, character, and attitude, while component three refers to various abilities at work, and component four involves professional and cultural knowledge. Through analysis and discussion, it is concluded that the key elements of college counselors’ core competencies include values, moral quality, vocational ability, and cultural knowledge, and a structural model of their core competencies is constructed.